Enhancing students' cognitive and science process skills through inquiry-based virtual experiments on electricity concepts - Rifat Shafwatul Anam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This study investigates the effectiveness of inquiry-based virtual experiments in improving elementary students' cognitive skills and science process skills in learning electricity concepts. The integration of digital simulations into elementary science instruction has become increasingly important for supporting conceptual understanding and scientific inquiry, particularly for abstract topics such as electricity. The population consisted of sixth-grade students at a public elementary school, from whom 25 were selected using purposive sampling based on technological readiness and curriculum alignment. The study employed a quasi-experimental design using a one-group pretest–posttest approach. The learning intervention was implemented through four inquiry-based sessions using PhET Interactive Simulations (Circuit Construction Kit: DC). Data were collected using two validated multiple-choice instruments: a 17-item cognitive test aligned with five levels of Bloom's Revised Taxonomy and an 18-item science process skills test measuring six indicators, including observing, classifying, predicting, interpreting data, drawing conclusions, and communicating. The instruments demonstrated good internal consistency (KR-21 = 0.83). Data were analyzed descriptively by comparing pretest and posttest scores. The results showed an increase in students' posttest mean scores, reaching 79.3% for cognitive skills and 73.1% for science process skills.